2013
DOI: 10.1007/s10815-013-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Attempted application of bioengineered/biosynthetic supporting matrices with phosphatidylinositol-trisphosphate-enhancing substances to organ culture of human primordial follicles

Abstract: PEG-fibrinogen hydrogels appear to have an advantage over alginate scaffolds for culturing human primordial follicles. Folliculogenesis is not increased in the presence of substances that enhance PIP3 production or with thin rather than thick sectioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…One report identified preantral follicles in human cortical strips cultured for only 6 days following activin stimulation [74]. Other studies, using a wide variety of culture conditions, report a range of successes, from tissue degeneration to appreciable follicle growth within 2 weeks [55,56,75,76]. Data described here support the premise that secondary follicles require approximately 3 weeks in culture to develop from primordial follicle-containing cortical strips, as this occurs in 4 out of 5 participant tissues.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…One report identified preantral follicles in human cortical strips cultured for only 6 days following activin stimulation [74]. Other studies, using a wide variety of culture conditions, report a range of successes, from tissue degeneration to appreciable follicle growth within 2 weeks [55,56,75,76]. Data described here support the premise that secondary follicles require approximately 3 weeks in culture to develop from primordial follicle-containing cortical strips, as this occurs in 4 out of 5 participant tissues.…”
Section: Discussionsupporting
confidence: 65%
“…This in situ approach has been applied with some success for human ovarian tissue [52][53][54][55] including encapsulating in a PEG-fibrinogen hydrogel [56]. We hypothesized that encapsulating small pieces of human ovarian cortex within alginate would provide additional physical support needed to maintain primordial follicles in culture.…”
Section: Human Ovarian Tissue Transported At 4°c For Up To 24 H Maintmentioning
confidence: 99%
“…However our study is not the first report of bpV(HOpic) treatment affecting human ovarian follicle development deleteriously. Lerer-Serfaty et al (2013) recently reported widespread follicle destruction in cryopreservedthawed human tissue exposed to a high concentration of 100 mM bpV(HOpic); this supports the view that manipulation of the PI3K pathway may also have negative impact on other signalling mechanisms (Blanco-Aparicio et al, 2007). Whilst PI3K activation and subsequent pAkt promotion by bpV(HOpic) can induce follicle activation in human ovarian tissue, it is possible that other Akt-independent effects of PTEN inhibition cause the follicle degeneration seen in this study and by other investigators (Lerer-Serfaty et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the role of PI3K/Akt in the pathology of cancer, the modulation of this pathway has been adopted as a potential approach for women with premature ovarian insufficiency (POI) and pregnancies have been achieved [34,113]. However, it has become increasingly evident that this pharmacological approach may be detrimental to oocyte/follicle development [29,[35][36][37]. We have demonstrated that dipotassium bisperoxo (5-hydroxypyridine-2-carboxyl) oxovanadate (bpv(HOpic)), a potent PTEN inhibitor, compromises the growth of apparently healthy human preantral follicles [36].…”
Section: The Pi3k/akt Pathway Links Primordial Follicle Growth and Thmentioning
confidence: 99%
“…Most importantly, pregnancies have been achieved in women following transplantation of small fragments of ovarian cortex after exposure to pharmacological inhibitors of PTEN [34]. Recent studies suggest that activation of follicles by these methods may be damaging to subsequent growth and survival of follicles [35][36][37], indicating that further investigation is required to fully understand the impact and implications of follicle activation using pharmacological manipulation of this pathway.…”
Section: Introductionmentioning
confidence: 99%